2017
DOI: 10.18052/www.scipress.com/ilns.61.43
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between C-Reactive Protein and Phytochemical(s) from <i>Calotropis procera</i>: An Approach on Molecular Docking

Abstract: Abstract. The present study was attempted to detect potential phytoconstituents in C. procera against inflammation and pain. CRP is known to be increased up to 10,000 fold when acute inflammation take place in human. The interaction between C-reactive protein and phytochemical(s) from Calotropis procera was carried out with the help of molecular docking by using PyRx software (Ver. 0.8) and LigPlot software (Ver. 1.4) to compare energy value and binding site of phytochemicals in reference to established synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Calotropis procera is an Indian tropical plant with important medicinal properties like anti-diabetic [13], hepatoprotective [14], anti-oxidant [15], anti-pyretic [16] and anti-fertility [17] activity. Molecular docking of few phytochemicals present in the latex of Calotropis procera has been reported to exhibit potent anti-inflammatory and analgesic activity [18][19][20]. Also, the latex of Calotropis procera significantly reduces cell influx, inflammatory mediators, oxidative stress and thereby improves locomotor dysfunction in complete Freund's adjuvant (CFA)induced arthritic rats [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Calotropis procera is an Indian tropical plant with important medicinal properties like anti-diabetic [13], hepatoprotective [14], anti-oxidant [15], anti-pyretic [16] and anti-fertility [17] activity. Molecular docking of few phytochemicals present in the latex of Calotropis procera has been reported to exhibit potent anti-inflammatory and analgesic activity [18][19][20]. Also, the latex of Calotropis procera significantly reduces cell influx, inflammatory mediators, oxidative stress and thereby improves locomotor dysfunction in complete Freund's adjuvant (CFA)induced arthritic rats [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Study on phytocompounds from T. arjuna with phosphodiesterase 5A, sodium-potassium pump and beta-adrenergic receptor showed that casuarinin showed multiple inhibitions on phosphodiesterase 5A and sodium-potassium pump, whereas Pelargonidin on phosphodiesterase 5A and beta-adrenergic protein targets [42]. Talapatra et al [43] reported that phytocompounds from Calotropis procera such as methyl myrisate (-3.0) and methyl behenate (-3.2), β-sitosterol (-5.6), uzarigenin (-5.5) and anthocyanins (-5.4) showed good binding with CRP receptors. Caffeic acid had remarkable interaction with proteins involved in inflammatory response (COX-2, COX-1, FXa and integrin αIIbβIII), thereby, having the potential to be developed as cardiovascular-safe anti-inflammatory medicine [44].…”
Section: Discussionmentioning
confidence: 99%